Impact of Chest Physiotherapy on Blood Oxygen Saturation Among Tuberculosis Inpatients at the West Sumatra Lung Hospital in 2025: Pengaruh Fisioterapi Dada Terhadap Saturasi Okigen Darah Pada Pasien Tuberkulosis Diruangan Rawat Inap Rumah Sakit Paru Sumatera Barat Tahun 2025 - Hardini, Sandra; Aisyah Nur, Siti; Masdalena; Wahyuningsih, Sri (Media Ekonomi Prabumulih, 2025)
The decrease in blood oxygen saturation in patients with Tuberculosis (TB) can lead to hypoxemia, which poses a serious risk to the patient's condition. One effective and easy-to-implement non-pharmacological intervention is chest physiotherapy, a series of nursing actions that include clapping and vibration. This study aimed to determine the effect of chest physiotherapy on blood oxygen saturation in pulmonary TB patients. The research was a quasi-experimental study using a one-group pretest-posttest design. It was conducted in the inpatient ward of West Sumatra Pulmonary Hospital from February 6th to March 7th in 2025, with a population of TB patients was 296 that recorded from January to June 2023. The sample was purposive sampling, 16 patients was in the experimental group. Data were analyzed using univariate and bivariate analyses with the Independent T-Test. The results of researh waas the average blood oxygen saturation before chest physiotherapy was 91.68%, and after the intervention, the average increased to 97.00%. Bivariate analysis indicated that chest physiotherapy had a significant effect on increasing blood oxygen saturation, with a p-value of 0.000 (p < 0.05). In conclusion, chest physiotherapy is effective in improving blood oxygen saturation in TB patients. Therefore, it is recommended that the West Sumatra Pulmonary Hospital implement a standard operating procedure (SOP) for chest physiotherapy as part of non-pharmacological care to help TB patients increase their blood oxygen levels.